Complex I and II Subunit Gene Duplications Provide Increased Fitness to Worms - Otero, Lucía; Martínez-Rosales, Cecilia; Barrera, Exequiel; Pantano, Sergio; Salinas, Gustavo (Frontiers in Genetics, 2019)
Helminths use an alternative mitochondrial electron transport chain (ETC) under hypoxic conditions, such as those found in the gastrointestinal tract. In this alternative ETC, fumarate is the final electron acceptor and rhodoquinone (RQ) serves as an electron carrier. RQ receives electrons from NADH through complex I and donates electrons to fumarate through complex II. In this latter reaction, complex II functions in the opposite direction to the conventional ETC (i.e. as fumarate reductase instead of succinate dehydrogenase). Studies in Ascaris suum indicate that this is possible due to changes in complex II, involving alternative SDHA and SDHD subunits derived from duplicated genes. We analyzed helminth genomes and found that distinct lineages have different gene duplications of complex II subunits (SDHA, SDHB, SDHC and SDHD). Similarly, we found lineage-specific duplications in genes encoding complex I subunits that interact with quinones (NDUF2 and NDUF7). The phylogenetic analysis of ETC subunits revealed a complex history with independent evolutionary events involving gene duplications and losses. Our results indicated that there is not a common evolutionary event related to ETC subunit genes linked to RQ. The free-living nematode Caenorhabditis elegans uses RQ and has two genes encoding SDHA (sdha-1 and sdha-2) and two genes encoding NDUF2 (nduf2-1 and nduf2-2). sdha-1 and nduf2-1 are essential genes and have a similar expression pattern during C. elegans lifecycle. Using knock out strains we found that sdha-2 and nduf2-2 are not essential, even in hypoxia. Yet, sdha-2 and nduf2-2 expression is increased in the early embryo and in dauer larvae, stages where there is low oxygen tension. Strikingly, sdha-1 and sdha-2 as well as nduf2-1 and nduf2-2 showed inverted expression profiles during the C. elegans life cycle. Finally, we found that nduf2-2 KO mutant strain progeny is affected. Our results indicate that different complex I and II subunit gene duplications provide increased fitness to worms.